2022
DOI: 10.1039/d2sc00918h
|View full text |Cite
|
Sign up to set email alerts
|

A bioorthogonal chemical reporter for the detection and identification of protein lactylation

Abstract: YnLac is an alkynyl-functionalized l-lactate analogue that is metabolically incorporated into l-lactylated proteins in live cells, enabling the fluorescence detection and proteomic identification of novel l-lactylated proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“… 232 With the help of other chemical tools such as alkynyl-functionalized bioorthogonal chemical reporter (YnLac), nonhistone Klac has also been reported by other studies in recent years. 233 , 234 The limited studies on nonhistone Klac have indicated its critical role in tumor, polymicrobial sepsis and retinopathy.…”
Section: Protein Acylation In Human Diseasesmentioning
confidence: 99%
“… 232 With the help of other chemical tools such as alkynyl-functionalized bioorthogonal chemical reporter (YnLac), nonhistone Klac has also been reported by other studies in recent years. 233 , 234 The limited studies on nonhistone Klac have indicated its critical role in tumor, polymicrobial sepsis and retinopathy.…”
Section: Protein Acylation In Human Diseasesmentioning
confidence: 99%
“…In addition, various reporter mole-cules such as fluorescent dyes and biotin can be orthogonally labeled on the tag sites via Click chemistry (copper(I)-catalyzed alkyne-azide cycloaddition, CuAAC reaction), making it possible to realize selective enrichment and visualization of metabolically tagged proteins. Despite these advantages, only a few substrates have been developed to metabolically tag acylated proteins, [27][28][29][30] and no substrates are available for lysine succinylation. Therefore, we aimed to develop a new substrate that enables comprehensive analysis of succinylated proteins and visualization of their intracellular distribution, which will contribute to unveiling the previously unknown phenomenon of protein succinylation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, lactylation modifications have primarily been studied on histones as of late, but we hypothesize that lactylation also occurs on non-histone proteins, similar to other modifications such as crotonylation. Additionally, the “YnLac” chemical reporter, which has an alkynyl functionalized bioorthogonal structure, may detect new lactylation modification sites in non-histone proteins ( Sun et al, 2022 ). In addition, several microbes and plants have also been identified with lactylated global proteins, including non-histone ( Gao et al, 2020 ; Zhang et al, 2021a ; Meng et al, 2021 ; Sun et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the “YnLac” chemical reporter, which has an alkynyl functionalized bioorthogonal structure, may detect new lactylation modification sites in non-histone proteins ( Sun et al, 2022 ). In addition, several microbes and plants have also been identified with lactylated global proteins, including non-histone ( Gao et al, 2020 ; Zhang et al, 2021a ; Meng et al, 2021 ; Sun et al, 2022 ). On the other hand, there are currently no investigations of non-histone lactylation in mammals, and additional research is required.…”
Section: Introductionmentioning
confidence: 99%